Immunomodulator and Antioxidant Effects of Saffron (Crocus sativus L.) on Diabetes Patients: a Literature Study - Septyana, Syifa Magita; Murtiningrum, Murtiningrum (Indonesian Journal of Food Technology, 2025)
Background: Saffron (Crocus sativus L.) has been traditionally used for its medicinal properties, including its potential to improve sleep quality and reduce anxiety. Recent studies have shown its potential in diabetes management, particularly through antioxidant and anti-inflammatory effects. Purpose: The aim of this study is to review the benefits of saffron in diabetes mellitus patients, both in experimental animals and humans. Method: A literature review method was used to analyze studies examining saffron’s effects on diabetes sufferers. Result: The results showed that saffron supplementation significantly reduced blood glucose levels, decreased oxidative stress markers such as malondialdehyde (MDA), and increased the activity of antioxidant enzymes such as catalase (CAT) and superoxide dismutase (SOD). Furthermore, saffron also enhances the expression of glucose transporter GLUT4 and AMP-activated protein kinase (AMPK). Saffron shows significant potential in managing diabetes by improving glucose metabolism, boosting antioxidant defenses, and reducing inflammation.